2022
DOI: 10.1155/2022/2585529
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis on Effects of Laparoscopic Total Hysterectomy Combined with High Hysterosacral Ligament Suspension in the Treatment for Uterine Prolapse

Abstract: Objective. To investigate the effect of laparoscopic total hysterectomy combined with high hysterosacral ligament suspension on the treatment for uterine prolapse. Methods. A total of 100 patients with uterine prolapse treated in our two hospitals from January 2019 to December 2021 were included in this study, which were divided into two groups through the number double-blind method, with 50 patients in each group. The control group was treated with transvaginal total hysterectomy, and the research group was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%